LEGAL BASIS AND PROBLEMS OF ORGANIZING INCLUSIVE EDUCATION IN THE REPUBLIC OF UZBEKISTAN (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article analyzes the regulatory legal acts on ensuring the educational rights of children with special educational needs, organizing inclusive education, as well as organizing inclusive education in the Republic of Uzbekistan.